Characterization of the TREM-1 signaling landscape in human neutrophils - Frederic Ries; Matthias Klein; Nora Rogmann; Sophie Többen; Federico Marini; Florian Heidel; Markus P. Radsak (PLoS ONE, 2026)
The Triggering Receptor Expressed on Myeloid Cells (TREM)-1 is a member of the Immunoglobulin superfamily, and an activating receptor mainly expressed on myeloid cells. Beyond its role in acute and chronic inflammatory processes, TREM-1 is also involved in cancer emergence and progression probably by alteration of the tumor-associated neutrophils (TAN) and macrophages (TAM). Advanced information about the TREM-1 signaling cascade may reveal novel targets for treating inflammatory and cancer diseases. As many specific kinase inhibitors are approved for treating various diseases, targeting kinases being active after TREM-1 ligation serves as a promising approach. Therefore, we investigated the protein tyrosine kinome (PTK) and serine threonine kinome (STK) by kinome activity profiling of purified human neutrophils after TREM-1 activation. As TREM-1 interacts with Toll-like receptor (TLR) 4 signaling, we used TLR4-activation by LPS to define TREM-1 specific pathways. We found an increased kinome activity after receptor ligation and could predict individual kinases. To gain further insights into the signaling cascade, we additionally investigated the transcriptomic profile that made us available to link the kinome activity to the resulting transcriptomic profile. In sum, we revealed several signaling pathways being active after TREM-1 ligation that are associated with various biological processed and diseases. This study facilitates selecting kinase inhibitors for further validation with the aim of targeting TREM-1 signaling in various inflammatory or cancer disease conditions.